2002
DOI: 10.1034/j.1600-0706.2002.990209.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact on fruit removal and seed predation of a secondary metabolite, emodin, in Rhamnus alaternus fruit pulp

Abstract: There are two contradictory approaches to explaining the presence of secondary metabolites in ripe fruits. One holds that they evolved toward enhancing dispersal success (adaptive approach); the other claims that they evolved primarily to deter herbivores from eating leaves and seeds and that their presence in ripe fruits is a byproduct of that function (non‐adaptive approach). We tested the validity of three hypotheses of the adaptive approach that explain the presence of secondary metabolites in ripe fruits.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 61 publications
0
37
0
1
Order By: Relevance
“…This concentration decreases to 2.5 ± 0.9 ppm in ripe black fruits. 75 Similar fruit color change also occurs in R. lycioides L., in R. punctata Boiss., and probably also in other Rhamnus species.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…This concentration decreases to 2.5 ± 0.9 ppm in ripe black fruits. 75 Similar fruit color change also occurs in R. lycioides L., in R. punctata Boiss., and probably also in other Rhamnus species.…”
Section: Resultsmentioning
confidence: 71%
“…It has been demonstrated for the Old World's Rhamnus alaternus and R. lycioides (R. palaestinus) and for the New World's R. cathartica that bird species do not consume unripe red fruits. 75,86,87 Emodin is the predominant secondary metabolite in Rhamnus fruits and recently it has been demonstrated that birds and small mammals are unable to detoxify high concentrations of emodin efficiently. 88 There are good indications for considerable predispersal seed predation in R. alaternus, 89 which may trigger the evolution of defense.…”
Section: Resultsmentioning
confidence: 99%
“…Abu-Darwish (2000) isolated and identified 11 compounds from barks of R. This study aimed to test the insecticidal activity of R. dispermus against the PTA, since it has been shown that Rhamnus spp. may contain compounds that act as botanical pesticides, such as emodin (Trial and Dimond, 1979, Singh et al, 1992, Tsahar, 2001Izhaki, 2002) Bark of R. dispermus was collected from AshShoubak, Jordan. Its botanical identification was confirmed by Dr. Talal Abu Rjae, at the University of Jordan, who keeps voucher specimens in his laboratory.…”
Section: Insecticidal Activity Of Rhamnus Dispermus Against Peach Trumentioning
confidence: 99%
“…Murray et al (1994) found that fruits of the family Solanaceae contained laxative chemicals that reduced seed retention time, while in contrast glycoalkaloids had a significant constipative effect on cedar waxwings Bombycilla cedrorum, increasing seed retention time (Wahaj et al 1998). Emodin, an anthraquinine present in fruits of the family Rhamnaceae, was found to increase gut retention time and food assimilation of yellow-vented bulbuls Pycnonotus xanthopygos (Tsahar et al 2002;Tsahar et al 2003); thus, the naturally low emodin concentration in fruits increases digestibility for these frugivorous birds (Tsahar et al 2003). …”
Section: Introductionmentioning
confidence: 99%